Vibrational analysis of boldine hydrochloride using QM/MM approach. Issue 5 (2010) - Misra, Neeraj; Siddiqui, Shamoon Ahmad; Srivastava, Ruby; Pandey, Anoop Kumar; Jain, Sudha
Abstract : A complete vibrational analysis was performed on the molecular structure of boldine hydrochloride using QM/MM method. The equilibrium geometry, harmonic vibrational frequencies and infrared intensities were calculated by QM/MM method with B3LYP/6-31G(d) and universal force field (UFF) combination using ONIOM code. We found the geometry obtained by the QM/MM method to be very accurate, and we can use this rapid method in place of time consuming ab initio methods for large molecules. A detailed interpretation of the infrared spectra of boldine hydrochloride is reported. The scaled theoretical wave numbers are in perfect agreement with the experimental values. The FT-IR spectra of boldine hydrochloride in the region 4000–500 cm –1 were recorded in CsI (solid phase) and in chloroform with concentration 5 and 10 mg/ml.